(untitled) (Journal of actual problems of jurisprudence, 2019)
In the article the problem of the definition of customs duties and their classification. In considering this issue have been analyzed the views and opinions of some legal scholars, conclusions are made. Key words: Customs, customs fees, duties, fees, customs.